Efektivitas Senam Lansia Terhadap Perubahan Depresi dan Kualitas Hidup Lansia - Ngadiran, Antonius; Eny Pujiati (Jurnal Kesehatan, 2024)
The prevalence of depression in the elderly population is estimated at 1-2%; the prevalence in women is 1.4% and in men 0.4%. Depression in the elderly needs to be prevented by using physical activity, one of which is exercise for the elderly.  The aim of the research is to prove that there is an influence of elderly exercise on changes in levels of depression and quality of life in the elderly. This research used a quasi-experimental design with a pretest and posttest approach, conducted on 73 elderly people divided into two groups: 36 elderly people in the intervention group and 37 elderly people in the control group. Data analysis used a research protocol; findings were analyzed with a significance level of <0.05%.   The  respondents participated in training 3x/week for 12 weeks. After doing the elderly exercise, there was a significant decrease in depression scores between the control and intervention groups with a p-value of 0.000. After doing elderly exercise, there was a significant increase in quality of life and there was a significant difference in changes in quality of life scores between the control group and the intervention group with a p-value of 0.010. Elderly people who participate in motor activity-based exercise (elderly exercise) regularly with a duration of 30 minutes per exercise, with a frequency of three times a week and a training duration of twelve weeks, have a better quality of life than those who do not participate in elderly exercise.